Graphene Modified Multifunctional Personal Protective Clothing. Issue 21 (20th August 2019) - Bhattacharjee, Shovon; Joshi, Rakesh; Chughtai, Abrar Ahmad; Macintyre, Chandini Raina
Abstract: Personal protective clothing is intended to protect the wearer from various hazards (mechanical, biological, chemical, thermal, radiological, etc.) and inhospitable environmental conditions that may cause harm or even death. There are various types of personal protective clothing, manufactured with different materials based on hazards and end user requirements. Conventional protective clothing has impediments such as high weight, bulky nature, lack of mobility, heat stress, low heat dissipation, high physical stress, diminishing dexterity, diminishing scope of vision, lack of breathability, and reduced protection against pathogens and hazards. By virtue of the superlative properties of graphene, fabrics modified with this material can be an effective means to overcome these limitations and to improve properties such as mechanical strength, antibacterial activity, flame resistance, conductivity, and UV resistance. The limitations of conventional personal protective equipment are discussed, followed by necessary measures which might be taken to improve personal protective equipment (PPE), the unique properties of graphene, methods of graphene incorporation in fabrics, and the current research status and potential of graphene‐modified performance textiles relevant to PPE. Abstract : Graphene‐modified protective clothing might overcome the limitations of conventional protective clothing, and demonstrate multifunctional properties. The limitations of present personal protective equipment (PPE), measures to improve PPE, and the evidence supporting the use of graphene to modify performance textiles relevant to PPE are discussed.